Perilaku Hidup Bersih dan Sehat (PHBS) di Desa Maccini Sombala Kecamatan Galesong Utara Kabupaten Takalar Sulawesi Selatan - Perdana, Satria; N, Nururrahmah; H, Hardi (Yayasan Daarul Huda Kruengmane, 2024)
Clean and Healthy Living Behavior (PHBS) must start from the household structure, because a healthy household is a capital asset for future development that needs to be maintained (Ministry of Health of the Republic of Indonesia, 2009). The management of improving PHBS is attempted starting from the smallest order, namely households, targeting individuals and families, then it will develop towards villages/sub-districts, sub-districts/health centers and healthy districts/cities until finally nationally it will be realized that all Indonesian people behave in a clean and healthy lifestyle. Healthy households are households that carry out 5 PHBS in the household, consisting of giving birth assisted by health workers, giving exclusive breast milk, weighing babies/toddlers every month, using clean water and washing hands with clean water and soap. PHBS indicators at the household level are very dependent on the awareness and active role of the community in their respective living environments.Efforts to increase healthy behavior in households have not shown optimal results, this can be seen, among other things, from the results of the 2018 Basic Health Research (RISKESDAS) which shows that in Indonesia only 39.1% of Indonesian households practice PHBS.